Research and education in robotics - EUROBOT 2010 international conference, Rapperswil-Jona, Switzerland, May 27-30, 2010 : revised selected papers - International Conference on Research and Education in Robotics Rapperswil-Jona, Switzerland) (2010; Obdrzalek, David; Gottscheber, Achim; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the proceedings of the International Conference on Research and Education in Robotics held in Rapperswil-Jona, Switzerland, in May 2010. The 17 revised full papers presented were carefully reviewed and selected from 24 submissions. They are organized in topical sections on mechanical design and system architecture, flexible robot strategy design, and autonomous mobile robot development.
Electronic reproduction.
Keywords: Robotics -- Congresses; Electronic books